Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. x(x-2)+x-2=0
=> (x-2).(x+1)=0
=> x-2=0 hoặc x+1=0
=> x=2 hoặc x=-1
b. 5x(x-3)-x+3=0
=> 5x(x-3)-(x-3)=0
=> (x-3).(5x-1)=0
=> x-3=0 hoặc 5x-1=0
=> x=3 hoặc x=1/5
\(a)\)\(x^3-x^2-x+1=0\)
\(\Leftrightarrow\)\(x^2\left(x-1\right)-\left(x-1\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)\left(x^2-1\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)\left(x-1\right)\left(x+1\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)^2\left(x+1\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}\left(x-1\right)^2=0\\x+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x=-1\end{cases}}}\)
Vậy \(x=1\) hoặc \(x=-1\)
Chúc bạn học tốt ~
a) \(x\left(x-2\right)+x-2=0\)
<=> \(\left(x-2\right)\left(x+1\right)=0\)
<=> \(\orbr{\begin{cases}x-2=0\\x+1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy...
b) \(5x\left(x-3\right)-x+3=0\)
<=> \(\left(x-3\right)\left(5x-1\right)=0\)
<=> \(\orbr{\begin{cases}x-3=0\\5x-1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=3\\x=\frac{1}{5}\end{cases}}\)
Vậy...
b) (x-3)2-(x-3)(x+3)=0
<=>(x-3)[(x-3)-(x+3)]=0
<=>(x-3)[x-3-x-3]=0
<=>(x-3)*(-6)=0
<=>x=3
a) (x-2)(x+2)-7=(x-1)2
<=>x2-4-7=x2-2x+1
<=>x2-11-x2+2x-1=0
<=>(x2-x2)+2x-11-1=0
<=>2x-12=0
<=>2x=12
<=>x=6
\(\left(x-3\right)\left(x+3\right)-\left(x-3\right)^2=0\Leftrightarrow\left(x-3\right)\left(x+3-x+3\right)=0\Leftrightarrow6\left(x-3\right)=0\Leftrightarrow x-3=0\Leftrightarrow x=3\)
Ta có: \(\left(x-3\right)\left(x+3\right)-\left(x-3\right)^2=0\)
\(\Leftrightarrow x^2-9-x^2+6x-9=0\)
\(\Leftrightarrow6x=18\)
hay x=3